A study on children’s rights protection in family aspects in Malaysia lessons for Zanzibar - Omar Hamdan, Sikujua; Che Soh @ Yusoff, Roslina; Mohd Zin, Najibah; Abdul Hak, Nora (International Knowledge Sharing Platform, 2018)
Children protection laws on family matters in Zanzibar has been recorded to have a lot of discrepancies. This is due to long-stand existing laws and the existing court hierarchy which exports the conflicts on the application of laws under various courts. However, many efforts have been made by the Zanzibar government to improve the standard on the laws of child protection rights, the existing conflicts between civil laws and shariah law has not comparatively received academic attention over the years in Zanzibar. The existing discrepancies greatly affect the children’s rights protection in many areas including family matters. Against this background, a critical exposition is made on the children protection laws on family matters in Malaysia with the purpose to learn and implement Zanzibar laws. The aim is to improve the Zanzibar laws of child protection in family aspects. This paper uses descriptive analysis of legal issues on children’s rights protection in family matters under the Malaysian laws and critical existing conflicts under Zanzibar laws.